Biochemical Basis of Obligate Autotrophy in Blue-Green Algae and Thiobacilli - Smith, Arnold J. (1967)
Differential rates of incorporation of sugars, organic acids, and amino acids during autotrophic growth of several blue-green algae and thiobacilli have been determined. In obligate autotrophs (both blue-green algae and thiobacilli), exogenously furnished organic compounds make a very small contribution to cellular carbon; acetate, the most readily incorporated compound of those studied, contributes about 10% of newly synthesized cellular carbon. In Thiobacillus intermedius, a facultative chemoautotroph, acetate contributes over 40% of newly synthesized cellular carbon, and succinate and glutamate almost 90%. In the obligate autotrophs, carbon from pyruvate, acetate, and glutamate is incorporated into restricted groups of cellular amino acids, and the patterns of incorporation in all five organisms are essentially identical. These patterns suggest that the tricarboxylic acid cycle is blocked at the level of α-ketoglutarate oxidation. Enzymatic analyses confirmed the absence of α-ketoglutarate dehydrogenase in the obligate autotrophs, and also revealed that they lacked reduced nicotinamide adenine dinucleotide oxidase, and had extremely low levels of malic and succinic dehydrogenase. These enzymatic deficiencies were not manifested by the two facultative chemoautotrophs examined. On the basis of the data obtained, an interpretation of obligate autotrophy in both physiological and evolutionary terms has been developed.